"We have either obsolete knowledge, obsolete equipment or obsolete skills": policy-makers and clinical managers' views on maternal health delivery in rural Nigeria. Issue 3 (3rd August 2021) - Udenigwe, Ogochukwu; Okonofua, Friday E; Ntoimo, Lorretta F C; Imongan, Wilson; Igboin, Brian; Yaya, Sanni
Abstract : Objective: The objective of this paper is to explore policy-makers and clinical managers' views on maternal health service delivery in rural Nigeria. Design: This is a qualitative study using key informant interviews. Participants' responses were audio recorded and reflective field notes supplemented the transcripts. Data were further analysed with a deductive approach whereby themes were organised based on existing literature and theories on service delivery. Setting: The study was set in Esan South East (ESE) and Etsako East (ETE), two mainly rural local government areas of Edo state, Nigeria. Participants: The study participants consisted of 13 key informants who are policy-makers and clinical managers in ESE and ETE in Edo state. Key informants were chosen using a purposeful criterion sampling technique whereby participants were identified because they meet or exceed a specific criterion related to the subject matter. Results: Respondents generally depicted maternal care services in primary healthcare centres as inaccessible due to undue barriers of cost and geographic location but deemed it acceptable to women. Respondents' notion of quality of service delivery encompassed factors such as patient-provider relationships, hygienic conditions of primary healthcare centres, availability of skilled healthcare staff and infrastructural constraints. Conclusion: This study revealed that while some key aspects of service delivery are inadequate in rural primary healthcare centres, there are promising policy reforms underway to address some of the issues. It is important that health officials advocate for strong policies and implementation strategies.